Characteristics of Reported Gonorrhea Diagnoses During The COVID-19 Pandemic Compared With Pre-COVID-19 Pandemic, Baltimore City, Maryland - Coen, Michelle E; Williford, Sarah L; Muvva, Ravikiran; Genberg, Becky; Greenbaum, Adena; Schumacher, Christina M (Sexually transmitted diseases, 2023)
Sexual health service disruptions due to COVID-19 mitigation measures may have decreased gonorrhea screening and biased case-ascertainment toward symptomatic individuals. We assessed changes in reported symptoms and other characteristics among reported gonorrhea cases during pandemic versus prepandemic periods in 1 city with persistent gonorrhea transmission. Enhanced surveillance data collected on a random sample of gonorrhea cases reported to the Baltimore City Health Department between March 2018 and September 2021 was used. Logistic regression assessed differences in case characteristics by diagnosis period (during pandemic: March 2020-September 2021; prepandemic: March 2018-September 2019). Analyses included 2750 (1090 during pandemic, 1660 prepandemic) gonorrhea cases, representing 11,904 reported cases. During pandemic versus prepandemic, proportionally fewer cases were reported by sexual health clinics (8.8% vs 23.2%), and more frequently reported by emergency departments/urgent care centers (23.3% vs 11.9%). Adjusting for diagnosing provider, fewer cases who were men with urethral infections (adjusted odds ratio [aOR], 0.65; 95% confidence interval [CI], 0.55-0.77), aged <18 years (aOR, 0.64; 95% CI, 0.47-0.89), and women (aOR, 0.84; 95% CI, 0.71-0.99) were reported, and cases with insurance (aOR, 1.85; 95% CI, 1.40-2.45), living with human immunodeficiency virus (aOR, 1.43; 95% CI, 1.12-1.83), or recent (≤12 months) gonorrhea history (aOR, 1.25; 95% CI, 1.02-1.53) were more frequently reported during pandemic versus prepandemic. Reported symptoms and same-day/empiric treatment did not differ across periods. We observed no changes in reported symptoms among cases diagnosed during pandemic versus prepandemic. Increased frequency of reported diagnoses who were insured, living with human immunodeficiency virus, or with recent gonorrhea history are suggestive of differences in care access and care-seeking behaviors among populations with high gonorrhea transmission during the pandemic.